Replication Data for "Estimating the Intrahousehold Costs and Benefits of Innovations to Enhance Smallholder Farmers’ Resilience" - International Food Policy Research Institute; University for Development Studies (International Food Policy Research Institute, 2023)
Replication data used to demonstrate the application of a new framework for cost-benefit analysis of climate information services (CIS) and other agricultural innovations aiming to improve smallholder farmers' resilience. The framework uses expected utility to quantify welfare benefits associated with non-monetary outcomes that are important from a development perspective, such as improved income smoothing, empowerment, and changes in time use. The data therefore collects variables such as risk preferences, income expectations, time use, and empowerment. The data were collected in November 2022 in the context of a CIS program in 6 regions in Ghana (Bono East, Central, Greater Accra, Northern, Upper East, and Upper West). Using computer-assisted personal interviews (CAPI), we surveyed male and female respondents from 661 households. We used multi-stage purposive sampling to select 11 districts, from which in total 38 villages were randomly selected. In each village, a sampling frame was developed with the help of community leaders, from which households were randomly selected for inclusion in the study.